2017
DOI: 10.1002/mpr.1601
|View full text |Cite
|
Sign up to set email alerts
|

Decision curve analysis as a framework to estimate the potential value of screening or other decision‐making aids

Abstract: Although screening has potential to increase detection of treatment, important subgroup differences exist. Greater consideration of responses to positive screens or alternatives to screening are needed to maximize the impact of efforts to improve detection and treatment of mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
(67 reference statements)
0
7
1
Order By: Relevance
“…While others have observed that individuals of an ethnic or racial minority are more likely to have a complex pathway to mental health care, including the police or other parts of the justice system (which could result in a higher prevalence), [47][48][49] a lower prevalence of mental illness among minority inmates (13%) than white (25%) or Aboriginal (23%) inmates was previously reported. 30 We did not observe other hypothesized ethnic disparities. For example, similar treatment access by white and Indigenous inmates is inconsistent with findings indicating lower treatment rates by Indigenous persons in New Zealand prisons.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…While others have observed that individuals of an ethnic or racial minority are more likely to have a complex pathway to mental health care, including the police or other parts of the justice system (which could result in a higher prevalence), [47][48][49] a lower prevalence of mental illness among minority inmates (13%) than white (25%) or Aboriginal (23%) inmates was previously reported. 30 We did not observe other hypothesized ethnic disparities. For example, similar treatment access by white and Indigenous inmates is inconsistent with findings indicating lower treatment rates by Indigenous persons in New Zealand prisons.…”
Section: Discussioncontrasting
confidence: 53%
“…While others have observed that individuals of an ethnic or racial minority are more likely to have a complex pathway to mental health care, including the police or other parts of the justice system (which could result in a higher prevalence), 47 49 a lower prevalence of mental illness among minority inmates (13%) than white (25%) or Aboriginal (23%) inmates was previously reported. 30…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations